Q: What is 2n squared plus 5n plus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5n + 12 = 3n Try to get all expressions with n on the left side 5n + 12 - 3n = 3n - 3n 2n + 12 = 0 Try to get rid of 12 on the left side 2n + 12 - 12 = -12 2n = -12 n = -12/2 = -6

2n/5 or 2/5n

-2

Oh, dude, adding n squared plus n squared is like adding apples to apples, you know? It's just like, you take two n squared terms and you add them together to get 2n squared. It's not rocket science, man. Just double up those n squares and you're good to go.

(n2 + 2n - 1) (n2 + 2n - 1) = n4 + 2n3 - n2 + 2n3 + 4n2 - 2n - n2 - 2n + 1 = n4 + 4n3 + 2n2 - 4n + 1 try with n = 5: (5 squared + 10 - 1) squared = 34 squared = 1156 with formula (5^4) + (4 *(5^3)) + (2 * (5^2)) - (4 * 5) + 1 = 625 + 500 + 50 - 20 + 1 = 1156

Related questions

It is: 2n^2 -5n -42 equals (2n+7)(n-6) when factored

n=1 2/3

-2n - 4p + 2. Without knowing n and p, that's the best you get.

5n+2n=7n If the variable is the same, n, then you can add the coefficients, 5 and 2. In General an+bn=(a+b)n FOR A CASE THAT DOES NOT WORK. 5n+2m=5n+2m You cannot combine unlike variables

5n + 12 = 3n Try to get all expressions with n on the left side 5n + 12 - 3n = 3n - 3n 2n + 12 = 0 Try to get rid of 12 on the left side 2n + 12 - 12 = -12 2n = -12 n = -12/2 = -6

4 = -5n + 6n2 if you want to solve for n: 6n2 - 5n - 4 = 0 (3n - 4)(2n + 1) = 0 3n - 4 = 0, n = 4/3 2n + 1 = 0, n = -1/2 n = {-1/2, 4/3}

2n/5 or 2/5n

5n - 9 = 2n + 6 : Add 9 to both sides 5n = 2n + 15 : Subtract 2n from both sides 3n = 15 : Divide both sides by 3 n = 5

7n -1n,0n,1n,2n,3n,4n,5n,6n,7n 1 2 3 4 5 6 7 8 9

-2

If the given equation were factorized it would be: 2n2 + 4n = 2n(n+1) Another Answer:- The given expression when factored is 2n(n+2)

9+2n=5n this is how you would set up the problem 9+2n-2n=5n-2n then you subtract the number with the variable on each side 9=3n this is what it leaves you with 9/3=3n/3 then you divide three by both sides to get the variable by itself 3=n then you have your answer Hope this helps you!!